Concordance of Chest Radiography and Chest Computed Tomography Findings in Patients with Hematologic Malignancy and Invasive Mucormycosis: What Are the Prognostic Implications? - Sebastian Wurster; Sung-Yeon Cho; Hazim Allos; Alexander Franklin; Dierdre B. Axell-House; Ying Jiang; Dimitrios P. Kontoyiannis (Journal of Fungi, 2024)
Invasive pulmonary mucormycosis (IPM) is a deadly opportunistic mold infection in patients with hematological malignancies (HM). Radiologic imaging is essential for its timely diagnosis. Here, we compared IPM lesions visualized by chest computed tomography (CCT) and chest X-ray (CXR) and determined the prognostic significance of discordant imaging. Therefore, we reviewed 44 consecutive HM patients with probable/proven IPM at MD Anderson Cancer Center in 2000–2020 who had concurrent CCT and CXR studies performed. All 44 patients had abnormal CCTs and 39 (89%) had anormal CXR findings at IPM diagnosis. However, only 26 patients (59%) showed CCT-matching IPM-suspicious lesions on CXR. Acute Physiology and Chronic Health Evaluation II score > 18 at IPM diagnosis and breakthrough infection to Mucorales-active antifungals were the only independent risk factors for 42-day and/or 84-day mortality. Absence of neutropenia at IPM diagnosis, neutrophil recovery in neutropenic patients, and surgical revision of mucormycosis lesions were protective factors. Although not reaching significance on multivariable analysis, visualization of CCT-matching lesions on CXR was associated with significantly increased 84-day mortality (log-rank test, p = 0.033), possibly as a surrogate of extensive lesions and tissue necrosis. This observation supports the exploration of radiologic lesion kinetics as a prognostic staging tool in IPM patients.